Implementasi Hak Imunitas DPR Ditinjau Berdasarkan Undang-Undang Nomor 17 Tahun 2014 Tentang MPR, DPR, DPD dan DPRD - Raphael, Axel (Res Publica: Jurnal Hukum Kebijakan Publik, 2025)
No one has the authority to revoke the right to total immunity. Although the right to qualified immunity is relative, it can still be denied if it is used "intentionally" to belittle or degrade another person's honor and dignity. This research discusses the implementation of the rights possessed by members of the People's Representative Council (DPR), namely the immunity rights regulated in Law Number 20 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, and the Regional Representative Council. In this research, the type of legal research that the author uses is normative legal research. The technique for collecting legal materials is carried out by studying literature which then uses the deductive method as an analysis technique. This research produces the author's views regarding the implementation of the right to DPR immunity which is reviewed based on Law Number 17 of 2014 concerning the MPR, DPR, DPD and DPRD..